PARTISIPASI PETANI ANGGOTA PERKUMPULAN PETANI PEMAKAI AIR (P3A) DALAM PENGELOLAAN AIR IRIGASI DI KECAMATAN PALAS KABUPATEN LAMPUNG SELATAN - Alviyanti, Wida; Nurmayasari, Indah; Prasmatiwi, Fembriarti Erry (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
Rice farmers uses irrigation water managed through Water UserÂ  Association (P3A). This study aims to analyze rice farming income, the level of participation, and factors related to the participation of farmers members of the P3A. Research data were collected in Palas Subdistrict, South Lampung Regency in November - December 2019. The number of respondents was 68 rice farmers members who were randomly selected. Primary data were obtained by interviewing the respondents and secondary data were obtained from several related institutions. The data were analyzed descriptively and using Rank Spearman correlation test. The results showed that rice farming in planting season 1 and 2 are profitable to cultivate. The levels of participation of P3A members in planning activities, implementing activities, monitoring and evaluating activities, and utilizing the results are in high category. The factors related to the participation of P3A members on irrigation management were the intensity of farmer interaction, the level of motivation, and land size.Â Key words: participation, Water User Association